State-Legal Regulation of Challenging Paternity and Motherhood - Natalia RAKSHA; Anna BORENSTEIN; Elena POZDNYAKOVA; Yulia VETCHINOVA; Natalia BARBASHOVA; Anastasia KOLMYKOVA (Communications of International Proceedings, 2021)
This article outlines the current legal problems of contestation paternity and maternity and offers the main prospects for their elimination. The priority character of marriage and family relations as one of the leading directions of social policy of any modern state predetermines the importance of challenging parental rights and obligations and makes this procedure a rather widespread phenomenon. It has been proved that against the background of active development of assisted reproductive technologies and increasing usage of surrogate motherhood services, the necessity of reviewing the legal status of surrogate mothers is imminent. It is concluded that it is expedient to inherit the legislative model of the Republic of Belarus regarding the necessity of imperative acknowledgment of the child born by the surrogate mother, its biological mother, and biological father as the parents. Under the conditions of foreign and Russian tendencies of gender equality, the point of view about the legislative consolidation of the possibility of using the surrogate motherhood program by single male persons has been substantiated. The problem of disputing maternity and paternity by germ cell donors whose material is used for in vitro fertilization (hereinafter referred to as IVF) has been analyzed. It is proved that the outlined problem has two aspects and assumes the necessity to include in the law the prohibition to contest maternity and paternity by donors as well as the use of a proxy from a spouse while executing IVF procedure. Using a wide range of comparative-legal and formal-legal (dogmatic) methods, there have been developed authors’ models of legislative constructions for a number of norms of the current legislation. The conclusions drawn in the course of this study can be used in further scientific, educational, and practical activities.
Keywords: Maternity - Paternity - Contestation - Surrogate Mother - Donor - Reproductive Technology